Invarianti strutturali nel governo del territorio - Maggio, Marvi (Territori, 2014)
The introduction of the concept of structural invariant in territorial and urban planning has encountered numerous application problems. The purpose of this work is to investigate the reasons and formulate a new definition capable of overcoming them. At the center of the analysis is the relationship between crucial concepts in the interpretation of the territory: development sustainability, resource, space, place, place identity, status, spatio-temporal territorial structures, and structural invariants intended as an instrument to produce and reproduce the social and environmental identity and quality of the territory. The fulcrum is the organization and functioning of the territory, the spatio-temporal processes and the actors who created them. And from intangible, but objective values, it is necessary to take the moves: the real estate values and the values attributed by the different population groups, in terms of memory, attribution of meaning and identity.